SEMICONDUCTOR DEPENDENCE AS CATALYST FOR THE PASSAGE OF JAPAN’S 2022 ECONOMIC SECURITY PROMOTION ACT - Sutardi, Ardra Mahatma Pratama; Pasha, Julian Aldrin (Universitas Padjadjaran, 2025)
This study examines how Japan’s semiconductor supply chain vulnerabilities exposed structural weaknesses in its traditional security strategy and catalyzed the 2022 Economic Security Promotion Act (ESPA). Using a qualitative analytical-descriptive approach, the research analyzes government reports, academic literature, and economic data to trace the evolution of Japan’s techno-nationalist orientation, which is defined as the pursuit of national security and autonomy through technological capability. The findings demonstrate that Japan’s deep reliance on foreign semiconductors, particularly advanced chips from Taiwan and rare earth elements from China, created strategic exposures that global shocks such as the COVID-19 pandemic and intensifying U.S.–China rivalry made increasingly untenable. These disruptions revealed the limits of Japan’s postwar model, which relied on market openness and U.S. security guarantees while outsourcing critical technological functions abroad. In response, Japan shifted toward a security-oriented techno-nationalism in which the state expands its role in safeguarding innovation ecosystems, reshoring production, and institutionalizing resilience. ESPA embodies this shift by securing critical supply chains, regulating strategic infrastructure, promoting next-generation technologies, and protecting sensitive intellectual property. Ultimately, Japan’s semiconductor crisis accelerated a paradigmatic transformation by embedding economic security, technological sovereignty, and techno-nationalist principles at the core of national security strategy. Studi ini menganalisis bagaimana kerentanan Jepang dalam rantai pasokan semikonduktor mengungkap kelemahan struktural dalam strategi keamanannya serta mendorong lahirnya Undang-Undang Promosi Keamanan Ekonomi (ESPA) 2022. Dengan menggunakan pendekatan kualitatif analitis-deskriptif, penelitian menelaah laporan pemerintah, literatur akademik, dan data ekonomi untuk memetakan evolusi orientasi tekno-nasionalis Jepang, yakni pandangan bahwa kemandirian dan keunggulan teknologi merupakan fondasi utama keamanan negara. Temuan menunjukkan bahwa ketergantungan Jepang pada chip canggih Taiwan dan mineral tanah jarang dari Tiongkok menciptakan kerentanan strategis yang semakin nyata akibat pandemi COVID-19 dan rivalitas teknologi AS–Tiongkok. Gangguan tersebut menyoroti keterbatasan model keamanan pascaperang Jepang yang mengandalkan keterbukaan ekonomi dan payung pertahanan AS sembari menempatkan fungsi teknologi kritis di luar negeri. Sebagai respons, Jepang bergerak menuju tekno-nasionalisme berorientasi keamanan, dengan memperluas peran negara dalam memperkuat ekosistem inovasi, meningkatkan produksi domestik, serta membangun ketahanan rantai pasokan. ESPA menginstitusionalisasi pergeseran ini melalui pengamanan produk strategis, regulasi infrastruktur penting, dukungan riset teknologi kritis, serta perlindungan kekayaan intelektual sensitif. Pada akhirnya, krisis semikonduktor mempercepat transformasi kebijakan Jepang, menempatkan keamanan ekonomi, kedaulatan teknologi, dan prinsip-prinsip tekno-nasionalisme sebagai inti strategi keamanannya.